2010
DOI: 10.1523/jneurosci.1248-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Structural Remodeling of Thalamocortical Synapses Parallels Experience-Dependent Functional Plasticity in Mouse Primary Visual Cortex

Abstract: Monocular lid closure (MC) causes a profound shift in the ocular dominance (OD) of neurons in primary visual cortex (V1). Anatomical studies in both cat and mouse V1 suggest that large-scale structural rearrangements of eye-specific thalamocortical (TC) axons in response to MC occur much more slowly than the shift in OD. Consequently, there has been considerable debate as to whether the plasticity of TC synapses, which transmit competing visual information from each eye to V1, contributes to the early function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
85
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 88 publications
14
85
0
Order By: Relevance
“…1 A-C). TTX is a long-lasting voltage-gated sodium channel blocker, and in agreement with previous studies (7,41), we found that a single dose completely abolished visual responses for 24-48 h, followed by a gradual recovery. In all MD cases, VEPs were recorded from V1 contralateral to the deprived eye (Fig.…”
Section: Monocular Deprivation Drives Lasting Visual Impairment In Micesupporting
confidence: 93%
See 1 more Smart Citation
“…1 A-C). TTX is a long-lasting voltage-gated sodium channel blocker, and in agreement with previous studies (7,41), we found that a single dose completely abolished visual responses for 24-48 h, followed by a gradual recovery. In all MD cases, VEPs were recorded from V1 contralateral to the deprived eye (Fig.…”
Section: Monocular Deprivation Drives Lasting Visual Impairment In Micesupporting
confidence: 93%
“…A single dose, administered by microinjection into the vitreous humor, can locally block all impulse activity in the optic nerve for a day or two. Of significance, inactivation of one eye with TTX fails to trigger depression of deprived-eye responses in V1 that is observed after comparable periods of monocular deprivation by lid closure or image blurring (5,7,(35)(36)(37). Thus, brief inactivation of both eyes with TTX could potentially augment recovery of function by lowering the plasticity threshold without the liability associated with other forms of deprivation.…”
Section: Significancementioning
confidence: 99%
“…Deprived eye depression pushes the OD ratio to 1 : 1 and this ratio is retained in the presence of the inhibitory cocktail, indicating that OD shifts can be fully accounted for through TC plasticity (figure 2d-f). This conclusion receives additional support from an ultrastructural study showing shrinkage and loss of TC synapses in layer 4 after only 3 days of MD [60]. Although these experiments do not provide any insights into the degree to which MD-induced plasticity is distributed across visual cortical excitatory and inhibitory circuit elements, they do demonstrate that there is no requirement for further plasticity to account for the full OD shift.…”
Section: Ocular Dominance Plasticitymentioning
confidence: 89%
“…Whether elimination and strengthening remain mechanistically related in the MNTB-LSO projection or become dissociated downstream of the Ca V 1.3-mediated signaling remains to be demonstrated. Likewise, it is unclear whether strengthening of immature GABA/glycinergic MNTB-LSO synapses precedes the elimination of redundant inputs, as was observed in other systems (Hashimoto and Kano, 2003;Coleman et al, 2010).…”
Section: Strengthening and Elimination Of Synaptic Connectionsmentioning
confidence: 97%